Designing an Android-Based Borneo Orangutan Adventure Game Using Scirra Construct 2 - Hotmian Sitohang (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2022)
Currently the game is very popular with many people. Because the game is a game that uses a smartphone that is easy to carry everywhere, the game is also a form of multimedia entertainment that is made as attractive as possible. Even game makers make it as interesting and fun as possible so that the general public can use it. In this study, the Borneo orangutan adventure game aims to introduce orangutans in Central Kalimantan and the life of orangutans. The benefits of this research are for entertainment media and the introduction of Bornean orangutans. This game is designed with multimedia software method. From the results of the black box test the application is in accordance with the purpose of making the game while the results of the questionnaire respondents with a Likert scale show that 91.2% are on a very good scale or satisfied in terms of the appearance of the game and the way the game operates.